The empty sleeve - Garfield, Leon. (New York : Delacorte Press, 1988)
Though he dreams of going to sea, fourteen-year-old Peter is not entirely displeased to be apprenticed to a locksmith, especially as it means getting away from his "saintly" twin; but when the ghost of a former apprentice and a murder put him in grave danger, it is only his despised brother who is able to save him.
Booklist.
Horn Book.
6.1
6.1
5-8.
5-8
Keywords: Apprentices -- Fiction; Brothers -- Fiction; Ghosts -- Fiction; Twins -- Fiction; Apprentices -- Fiction; Brothers -- Fiction; Ghost stories; Twins -- Fiction; England -- Fiction